2015
DOI: 10.1080/01446193.2015.1050966
|View full text |Cite
|
Sign up to set email alerts
|

Exploring industrialized housebuilders’ interpretations of local requirements using institutional logics

Abstract: Industrialized housebuilding contractors use standardized processes and building systems to improve time and cost efficiency. Recent governmental investigations argue that Swedish local planning authorities' requirement setting practices stifle the potential for increased industrialization. Yet, no previous research has accounted for the industrialized housebuilders' perspective. We aim to explore industrialized housebuilders' interpretations of local requirement setting, using institutional logics to increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Specific customer requirements and site conditions (Aitchison 2017) are typical examples. Moreover, Viking and Lidelöw (2015) identify the interpretive local requirement setting as detrimental in the IHB context. An interpretive local requirement setting occurs when local planning authorities, who are in charge of issuing building permits, interpret legal requirements and codes in a different way than an IHB company does.…”
Section: Business Models and The External Business Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Specific customer requirements and site conditions (Aitchison 2017) are typical examples. Moreover, Viking and Lidelöw (2015) identify the interpretive local requirement setting as detrimental in the IHB context. An interpretive local requirement setting occurs when local planning authorities, who are in charge of issuing building permits, interpret legal requirements and codes in a different way than an IHB company does.…”
Section: Business Models and The External Business Environmentmentioning
confidence: 99%
“…Business models are the field of research that connected product platforms and the external business environment in the IHB context (Brege et al 2014, Lessing and Brege 2015, Lessing and Brege 2018. The terminology regarding the external business environment in the project dimension of IHB was adopted from Viking and Lidelöw (2015) and Aitchison (2017). The units of analysis were revised to the state as presented in the frame of reference and applied on empirical data in conducting analysis and synthesis iteration (Step 6).…”
Section: Data Collection and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding stakeholders' requirements and expectations is a key task of stakeholder analysis. Prior studies reported OSM customers' expectations and requirements in several countries/regions (Armacost et al 1994;Phillips et al 2016;Viking and Lidelöw 2015;Švajlenka and Kozlovská 2018b). For instance, Armacost et al (1994) revealed that the customers' needs referred to the style, process technology, materials, performance feature and functionality in the US manufactured housing market.…”
Section: Stakeholders' Requirements and Expectationsmentioning
confidence: 99%
“…Regarding multiplicity in decision-making, Hedgren and Stehn (2014) and Viking and Lidelöw (2015) found that actors manage multiple meanings in adopting infrastructure development and maintenance. On the other hand, they are eager to join us in our pursuit of academic development in order to fathom the mysteries of the construction industry and finally go beyond the common sense in order to actually bring about change in our sector.…”
Section: Other-than-rationality and Multiplicity In Construction Manamentioning
confidence: 99%